2-[18F]Fluoroethyl tosylate – a versatile tool for building 18F-based radiotracers for positron emission tomography. Issue 10 (28th September 2015) - Kniess, Torsten; Laube, Markus; Brust, Peter; Steinbach, Jörg
Abstract : The review highlights the role of 2-[ 18 F]fluoroethyltosylate ([ 18 F]FETs) in PET radiotracer design since it is a preferred labeling reagent according to its high reactivity to phenolic, amine, thiophenolic and carboxylic functions. Abstract : Positron emission tomography (PET) is a modern in vivo imaging technique and an important diagnostic modality for clinical and pre-clinical research. The incorporation of a radionuclide like fluorine-18 into a target molecule to form PET radiopharmaceuticals is a repeated challenge for radiochemists. [ 18 F]Fluoroethylation is a well-acknowledged method for 18 F-radiolabeling and 2-[ 18 F]fluoroethyl tosylate ([ 18 F]FETs) is a preferred reagent because of its high reactivity to phenolic, thiophenolic, carboxylic and amide functionalities. This review will highlight the role of [ 18 F]FETs in PET chemistry and summarize its applicability in radiotracer design. The radiolabeling conditions and the pros and cons of direct and indirect radiolabeling as well the aspects of the reactivity of [ 18 F]FETs compared with other [ 18 F]fluoroalkylating reagents will be discussed comprehensively.